Taxation of Litigation Costs under Uniform Rule 70: Attorneys Acting as Counsel are Entitled to Equal Reimbursement for Equal Work by Advocates - Fareed Moosa (Potchefstroom Electronic Law Journal, 2023)
Unlike during the apartheid era, high courts are no longer the terrain of advocates solely. By law, qualifying attorneys have a right of audience there. When attorneys render services usually performed by advocates and they secure a party-and-party costs order for their clients, then a question arising is whether the unsuccessful litigant is liable to indemnify the successful litigant on the lower tariff ordinarily applicable to attorneys' fees under Uniform Rule 70, or the higher tariff of reasonable fees applied to advocates under Uniform Rule 69. This important issue in the law of costs forms the core subject of this article. It engages therewith through a critical analysis of the prevailing case law dealing with Uniform Rule 70(3) read with Uniform Rule 70 tariff item A(10), as well as an application of the mandatory interpretive directive in section 39(2) of the Constitution of the Republic of South Africa, 1996 taken with the tools of textual, contextual and purposive interpretation.